2017
DOI: 10.1016/j.tig.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Mosaicism in Preimplantation Human Embryos: When Chromosomal Abnormalities Are the Norm

Abstract: Along with errors in meiosis, mitotic errors during post-zygotic cell division contribute to pervasive aneuploidy in human embryos. Relatively little is known, however, about the genesis of these errors or their fitness consequences. Rapid technological advances are helping close this gap, revealing diverse molecular mechanisms contributing to mitotic error. These include altered cell cycle checkpoints, aberrations of the centrosome, and failed chromatid cohesion, mirroring findings from cancer biology. Recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
150
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(168 citation statements)
references
References 112 publications
(172 reference statements)
5
150
0
Order By: Relevance
“…Such mitotic aneuploidies may propagate to descendant cells in a clonal manner and may also contribute to fitness variation. While severe chromosomal mosaicism is lethal to early embryos (McCoy et al 2015b;Ottolini et al 2017) , low levels of mosaicism appear compatible, and perhaps even common, with live birth (Greco et al 2015;McCoy 2017) .…”
Section: Introductionmentioning
confidence: 99%
“…Such mitotic aneuploidies may propagate to descendant cells in a clonal manner and may also contribute to fitness variation. While severe chromosomal mosaicism is lethal to early embryos (McCoy et al 2015b;Ottolini et al 2017) , low levels of mosaicism appear compatible, and perhaps even common, with live birth (Greco et al 2015;McCoy 2017) .…”
Section: Introductionmentioning
confidence: 99%
“…This type of analysis can also identify sex chromosome mosaicism (Johnson et al 2010;Fragouli 792 et al 2011;McCoy 2017) and large structural variants involving the sex chromosomes. In the 793 results section we have shown that mosaics are outliers from the four defined clusters 794 observed in the intensity based chromosome sex determination plot (Figure 1).…”
Section: Minimuga As a Tool For Discovery 781mentioning
confidence: 99%
“…These repetitive arrays and the flanking 5 segments, together the Centromere Proximal Regions (CPRs), play critical roles in the integrity of mitotic and meiotic inheritance (2). In somatic tissues, chromosome instability, including loss and gain of chromosomes, plays large and complex roles in aging, cancer (3), and human embryonic survival (4). Sequence variation in CPRs can affect meiotic pairing (3,4), kinetochore formation (5,6) and nonrandom segregation (3,4,6).…”
Section: Main Textmentioning
confidence: 99%
“…In somatic tissues, chromosome instability, including loss and gain of chromosomes, plays large and complex roles in aging, cancer (3), and human embryonic survival (4). Sequence variation in CPRs can affect meiotic pairing (3,4), kinetochore formation (5,6) and nonrandom segregation (3,4,6). Aneuploidy in the germline, typically 10 arising during meiosis, is a large component of genetic disease (9).…”
Section: Main Textmentioning
confidence: 99%